Combination of Dietary Ahiflower Oil and Equol Enhances Long‐Chain Polyunsaturated Fatty Acid Levels in Rainbow Trout Tissues. Issue 11 (5th February 2019) - Fickler, Anna; Staats, Stefanie; Michl, Stéphanie Céline; Hasler, Mario; Rimbach, Gerald; Schulz, Carsten
Abstract: Equol and Ahiflower oil have been shown to increase either eicosapentaenoic acid (EPA, 20:5n‐3) or docosahexaenoic acid (DHA, 22:6n‐3) levels in tissues of rainbow trout when applied individually. Thus, we investigated whether the combination of an Ahiflower oil‐based diet and equol might increase both, EPA and DHA levels, in rainbow trout. Rainbow trout (87.1 ± 0.3 g) were fed with five diets for 8 weeks. A diet based on a blend of fish and vegetable oils (FV) served as a reference diet. The four experimental diets contained a blend of Ahiflower oil and vegetable oils (AV). The AV‐diets were supplemented with equol by 0.0%, 0.1%, 0.2%, and 0.3% DM of the diet (AV‐C, AV‐EQ1, AV‐EQ2, and AV‐EQ3). The dietary treatments did not affect growth performance of fish and chemical nutrient composition of the whole body samples. Fish fed with the equol diets showed dose‐dependently increased liver weights and 18:0 liver levels. The content of EPA showed no consistent pattern between tissues but all AV‐groups were characterized by higher liver EPA values than FV. DHA values of AV‐EQ2 and AV‐EQ3 were similar to FV in fillet, tended to be the highest in the whole body and were significantly higher in liver compared to FV. In contrast, mRNA steady state levels of fatty acyl desaturase 2a (delta‐6) [ fads2a(d6) ] were not affected by the dietary treatments. In conclusion, the combination of dietary Ahiflower oil and equol (0.2% and 0.3%) seems to affect the fatty acid metabolism of rainbow trout positively to increase DHA tissue levels.